Development of Learning Media "Geoscan" Related to Geographical Characteristics of Indonesia as an Archipelago and Its Influence on Aspects of Life in Grade V Theme 1 - Alfiana Silvi Damayanti; Amalia Nur Alam; Anin Syafatia Rahma; Islam Dewana Bintang; Umi Amiroh Dwi Herawati (Journal of Software Engineering, Information and Communication Technology (SEICT), 2023)
The use of the application aims to make the essence of learning effectively received by students, one of which we will discuss is the material "Geographical Characteristics of Indonesia as an Archipelago and its Effect on Life". Geographical conditions reflect an integration of regions, namely how the regions are arranged by physical and social symptoms. Therefore, this research discusses the Multimedia Development Life Cycle (MDLC) method. From the research that has been done, it can be concluded that making an application called GEOSCAN by utilising barcode scans in learning grade V Theme 1 SD about "Geographical Characteristics of Indonesia as an Archipelago and its Influence on Life." and in grade 5 social studies subjects about "Geographical characteristics of Indonesia as an archipelago / maritime and agrarian country and its influence on economic, social, cultural, communication and transportation life". This research is intended to help facilitate delivery and achieve learning objectives. This application is made through Unity, in its use students can open the application, scan maps, and access material on the geographical conditions of the five major islands in Indonesia.